2002
DOI: 10.1021/jp0203393
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Lattice Displacement by Pulse Thickness Extension Mode Resonance Oscillation of Acoustic Wave and Its Effect on the Activity for Ethanol Oxidation of a Thin Pd Film Catalyst

Abstract: Pulse radio frequency (rf) electric power was applied to a ferroelectric single crystal of z-cut LiNbO3 to generate pulse thickness extension mode resonance oscillation (p-TERO) of bulk acoustic wave, and the effects of p-TERO on the catalytic activity for ethanol oxidation of a Pd catalyst deposited on the crystal were studied. The employment of the pulse method made it possible to introduce several times larger rf power to the catalyst, compared to conventional continuous rf power introduction. The p-TERO re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…To establish much larger catalyst activation by the TERO effects, the achievement of as large lattice displacement as possible at high resonance frequency is desirable. Previously, for ethanol oxidation on a Pd catalyst, we have demonstrated that a pulse TERO yields the high catalyst activation . Thus, it is interesting to apply a pulse TERO of high resonance frequency to catalyst activation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To establish much larger catalyst activation by the TERO effects, the achievement of as large lattice displacement as possible at high resonance frequency is desirable. Previously, for ethanol oxidation on a Pd catalyst, we have demonstrated that a pulse TERO yields the high catalyst activation . Thus, it is interesting to apply a pulse TERO of high resonance frequency to catalyst activation.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, for ethanol oxidation on a Pd catalyst, we have demonstrated that a pulse TERO yields the high catalyst activation. 21 Thus, it is interesting to apply a pulse TERO of high resonance frequency to catalyst activation. Furthermore, an interesting comparative study is to employ ferroelectric crystals with different crystal thickness that permits us to change resonance frequency as the other method.…”
Section: Discussionmentioning
confidence: 99%
“…By assuming uniform lattice atom expansion, we calculated a change in surface atom−atom distance due to the largest lattice displacement to be less than 10 -5 % . Thus, it is unlikely that the geometric site effects relating to bond lengthening or shortening of surface atoms are directly responsible for work function shifts.…”
Section: Discussionmentioning
confidence: 99%
“…[24,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Cai et al studied the dissociation and oxidation of ethanol on aP de lectrode in 0.1 m NaOH by combining in situ attenuated total reflection surfaceenhanced infrared absorption spectroscopy (ATR-SEIRAS)w ith H-D isotope replacement, focusing on the identification of the chemicaln ature of pivotal intermediates in differentr eaction pathways. [24,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Cai et al studied the dissociation and oxidation of ethanol on aP de lectrode in 0.1 m NaOH by combining in situ attenuated total reflection surfaceenhanced infrared absorption spectroscopy (ATR-SEIRAS)w ith H-D isotope replacement, focusing on the identification of the chemicaln ature of pivotal intermediates in differentr eaction pathways.…”
Section: Platinum and Palladiummentioning
confidence: 99%
“…Palladiumh as also received much attention as ap ossible economical substitute for rarep latinum for electrocatalyzing the oxidation of ethanol. [24,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Cai et al studied the dissociation and oxidation of ethanol on aP de lectrode in 0.1 m NaOH by combining in situ attenuated total reflection surfaceenhanced infrared absorption spectroscopy (ATR-SEIRAS)w ith H-D isotope replacement, focusing on the identification of the chemicaln ature of pivotal intermediates in differentr eaction pathways. [98] As suggested by the reaction pathways outlined in Figure 3, they found that ethanol may be dehydrogenated at a-C to form adsorbed acetyl rather than acetaldehyde, followed by successive decomposition to C 1 species, including CO ad and CH x at open-circuit potential or lower potentials.…”
Section: Platinum and Palladiummentioning
confidence: 99%